Wear behaviors and high-temperature oxidation resistance properties of tantalum carbide layer. Issue 23 (1st December 2021) - Di, Chongqing; Yan, Xiaodong; Yang, Yin; Ye, Wei; Zhao, Manyuan; Li, Defu
Abstract: A TaC/Ta2 C bilayer is obtained by vacuum carburizing technology and characterized by scanning electron microscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction, the nano-indentation, friction and wear test, high-temperature oxidation experiment. XPS analyses indicate that the carburized layer is composed of intermediate layer Ta2 C and outer-layer TaC. The total thickness of the carburized layer is approximately 20 μm. The nano-indentation hardness of the carburized layer along the depth direction varies from 14.632 to 35.832 GPa. The formation of the hard phase in carbide considerably improves the wear resistance of pure Ta. The high-melting-point ceramic phase in carbide improves the high-temperature oxidation resistance of pure Ta, thereby making it serve in high-temperature air environment for a short time.